KINERJA PEGAWAI KANTOR PELAYANAN PAJAK (KPP) PRATAMA PEKANBARU TAMPAN DALAM MELAYANI WAJIB PAJAK - Pranata, Deni; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Employee Performance Tax Office (LTO) Pratama Pekanbaru Tampan In Serving Taxpayers. This study aims to determine the performance and the factors that affect employee performance Tax Office (LTO) Primary Handsome Pekanbaru in serving taxpayers. This study uses a quantitative research study deskriptif. The way to collect the data the authors used a questionnaire and observation as a data collection tool research. After collecting data from survey respondents are employees of the Tax Office Primary Pekanbaru and taxpayer maintains in Pekanbaru tax service office on performance variables consisting of 6 indicators of Work Quality, Quantity of Work, Timeliness, Effectiveness Resources, Independence and motivation , it can be seen that the performance of which is owned by an employee in the office of serving taxpayers in both categories, as for some of the factors that influence employee performance is the human resources of the organization and work organization with the system. So once held research can be in the know that the Employee Performance Tax Office (LTO) Pekanbaru Tampan In Serving Taxpayers in both categories .Keywords : Performance , Employee Services